Soft Power, Confucius Institute and China’s Cultural Diplomacy in Malaysia - Ngu Ik Tien; Ngeow Chow Bing (Kajian Malaysia, 2026)
The point of departure in this study is to assess the effectiveness of China’s cultural diplomacy in Malaysia by looking at the employment of three main strategies and its limitations. The study utilises the methods of interview and empirical case study by firstly, giving a detailed look into the Kong Zi Institute (Confucius Institute) in Malaysia, and secondly, investigating some rarely-noticed diplomatic undertakings from the provincial or city governments of China. While the Confucius Institute and some image-building efforts represents the aspect of China’s central government’s soft power policy in Malaysia, the Chinese officials from local governments tend to focus on cultural and economic initiatives with the ethnic Chinese social organisations in Malaysia. After examining the Kong Zi Institute and discussing China’s provincial-local governments’ cultural outreach activities, the third aspect that this article examines is the narrative of Chinese Dream propagated by the Chinese officials in Malaysia. The article ends with an assessment of Malaysian perceptions and responses towards the Chinese official initiatives. Overall, the impact of China’s cultural diplomacy, either the Confucius Institute or other initiatives, in raising the positive image of China, may not be said to be either a success or failure. Malaysian’s positive image of China may have been caused by other factors not directly related to China’s cultural diplomacy, but other factors, including the foreign policy of China and the remarkable economic achievement.